A new pleuromutilin candidate with potent antibacterial activity against Pasteurella multocida. (February 2019) - Fu, Yunxing; Ma, Lijun; Yi, Yunpeng; Fan, Yuan; Liang, Jianping; Shang, Ruofeng
Abstract: This study assessed the antimicrobial activity of 14-O-[(4, 6-Diaminopyrimidine-2-yl) thioacetyl] mutilin (DPTM), a novel pleuromutilin candidate with a substituted pyrimidine moiety, against Pasteurella multocida . Minimum Inhibitory Concentration (MIC), Oxford Cup assay, and time-kill experiments were used to measure the activity of DPTM against P. multocida serotype A in vitro . We observed that DPTM was potent against Pasteurella multocida serotype A with the MIC value of 0.781 μg/mL. The mean inhibition-zone diameters of DPTM (50, 25, and 12.5 μg/mL) were 29.4, 24.2 and 20.1 mm, respectively. Time-kill experiments showed that the drug caused a rapid decline in the number of bacteria compared with the initial inoculum at 4 h and killed 94.6% of the bacteria during 24 h. Furthermore, DPTM activity was also assessed in a lung infection model challenged with 4.0 × 10 9  CFU/mL P. multocida serotype A. The results showed that DPTM significantly reduced mortality rate and bacterial load, and alleviated the pathological changes of lung. The antibacterial effect of DPTM found in this study suggested that it was useful in the prevention or control of pneumonia caused by P. multocida . Graphical abstract: Image 1 Highlights: 14-O-[(4, 6-Diaminopyrimidine-2-yl) thioacetyl] mutilin (DPTM) was proved most potent antibacterial agent against P. multocida in vitro assays. Time-kill experiments showed DPTM inhibited P. multocida dependent on concentration. DPTM showed higher inhibition efficacy against P. multocida in vivo assays in mice, which could significantly reduce mortality rate and bacterial load, and alleviate the pathological changes of lung.